آليات تدقيق الدراسات والمشاريع المعمارية - فاكوش, عقبة (Latakia University Journal -Engineering Sciences Series, 2019)
يمر المشروع الهندسي بمراحل عدة حتى يصل إلى مرحلة التنفيذ. هذه المراحل تبدأ من اختيار المشروع وموقعه إلى الدراسة المساحية والطبوغرافية إلى علاقة هذه المنشأة بالوسط المحيط وصولاً إلى الدراسة المعمارية والاختصاصات الأخرى؛ والمرحلة الأهم هنا هي مرحلة التدقيق، وهذه المرحلة في أغلب الأحيان لا تعطى حقها من الرعاية الكافية، إذ تدرج مرحلة تدقيق الدراسات والمشاريع المعمارية ضمن اختصاصات المهندس الاستشاري المعماري، ولكن تكمن المشكلة أن الطرق المتبعة لهذه العملية محلياً تختلف عما هو متبع إقليمياً وعالمياً. يأخذ البحث أهميته من خلال مكانة عملية تدقيق المخططات والتصاميم والتأكد من صحة الدراسة ومطابقتها للواقع على أنها اللبنة الأساس في نجاح أي مشروع، ويتوجه البحث إلى تكوين انطلاقة من أجل وضع أسس ثابتة للتدقيق لا تجعل مجالاً لأي لبس أو اجتهادات من أجل إنجاز عملية التدقيق المعماري والعمراني، آخذين بالاعتبار الجهات المدققة كافة واعتبار تلك الأجزاء من التدقيق جزءاً لا يتجزأ من الإضبارة المتكاملة لأي مشروع هندسي ووضع آلية منهجية علمية لإجراء عملية التدقيق للمشاريع المعمارية. The engineering and architectural project should be processed at several levels to reach the stage of implementation. These phases start from the project selection and location to the spatial and topographic studies, and cover the relationship with environment under the architectural study and other specialties. The most important stage here is the stage of auditing; this stage is often not given its due care, and it might be ignored sometimes . The stage of auditing the architectural projects studies is included in the consulting stage for which the architect is responsible. So the problem lies in the fact that the local methods used for this process are different from what is used regionally and globally. The importance of the research lies in having the auditing of plans and designs, the validation of the study, and its conformity to reality as major concepts of the project's success. It seeks to set principles of auditing to avoid confusion in the process of the architectural and urban studies. Considering all reviewers and checking items as major points of any integrated engineering projects record, it configures practical means of evaluating the architectural solutions.